(untitled) (Damu Journal of Sport Sciences, 2025)
Self-talk is an important psychological factor that influences athletic performance, as it is used as a means of self-motivation and enhancing confidence. In team sports such as volleyball, self-talk can significantly impact individual and group performance. This research aims to study the effect of a set of exercises to help develop self-talk and basic skills for female volleyball students. The research problem was that many female students in physical education had difficulty acquiring the required basic skills and performing exercises efficiently. The researcher aimed to develop specific exercises using tools to help develop self-talk and basic volleyball skills for female students. The research population included 20 third-year female students at the College of Education for Girls. They were divided into two groups: 10 students in the experimental group and 10 students in the control group. Questionnaires were used to measure self-talk, and tests were used to assess basic skills. A training program including self-talk exercises and the skills studied was administered to the experimental group for six weeks, while the control group continued training provided by the subject instructor for the same period. The research results showed that the auxiliary exercises had a positive effect on self-talk, leading to improved basic volleyball skills. Therefore, enhancing self-talk is considered an essential part of sports training. The most important recommendations were: The auxiliary exercises proved effective in improving the level of positive self-talk among students, which positively impacted psychological and skill performance, enhancing the students' ability to perform basic volleyball skills more efficiently.